Efektywność inwestowania w mienie prywatyzowanych przedsiębiorstw - Pawłowski, Janusz (Effectiveness of Investing in the Property of Privatised Enterprises, 2005)
In this article the conception of appreciation of investments effectiveness in privatised corporations is presented, basing on three categories: analysis of costs of obtaining tangible capital, analysis of corporations competitiveness after privatisation process and classical calculation of financial investment effectiveness.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 301-314